Developing future scenarios for climate-smart agriculture and food security - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
With the help of researchers from the University of Oxford, CCAFS designed a participatory and interactive method to develop future scenarios for agricultural development and food security. This initiative brought together policymakers, researchers, private sector partners, NGOs, and other stakeholders to build future scenarios for South Asia that look at social, political and economic uncertainties in agricultural development and food security under climate change.